Parental and child's psychosocial and financial burden living with an inherited metabolic disease identified by newborn screening - Schnabel-Besson, Elena; Garbade, Sven; Gleich, Florian; Grünert, Sarah; Krämer, Johannes; Thimm, Eva; Hennermann, Julia B.; Freisinger, Peter; Burgard, Peter; Gramer, Gwendolyn; Morath, Marina; Tuncel, Ali Tunç; et al. (Journal of inherited metabolic disease, 2025)
Newborn screening (NBS) is one of the most effective measures of secondary prevention. While the benefit of NBS on the clinical long-term outcomes of children with inherited metabolic diseases (IMD) has been demonstrated, the potential burden of families living with an early diagnosed and treated child with an IMD has not been thoroughly investigated. The aim of this longitudinal questionnaire-based study on 369 families living with a child with an IMD was to investigate the psychosocial and financial burden following a true-positive NBS. The reported psychosocial burden differed between children and their parents, and was associated with the child's age, diagnosis, and treatment. At younger ages, parent-reported burden was higher for the parents than for the individual child, while it increased for children and decreased for parents as the child grew older. Furthermore, psychosocial burden increased if the child required a strict dietary treatment and was at risk of metabolic decompensation. Regardless of diagnosis and treatment, the developmental delay of their child independently increased the parental psychosocial burden. Financial burden was reported by 24% of all families, and was higher in low-income families and in families whose children required dietary treatment. In conclusion, a substantial psychosocial and financial burden was revealed for children and their families after true-positive NBS. Since this burden is likely to have a negative impact on the long-term individual health benefits of NBS, this study underlines the importance of regularly assessing the psychosocial and financial needs of these families.
Zuerst veröffentlicht: 27. August 2024
Gesehen am 05.09.2025